2024
DOI: 10.7150/ijms.89370
|View full text |Cite
|
Sign up to set email alerts
|

NAD+-A Hub of Energy Metabolism in Heart Failure

Yaoxin Wu,
Zuowei Pei,
Peng Qu

Abstract: Heart failure is a condition where reduced levels of adenosine triphosphate (ATP) affect energy supply in myocardial cells. Nicotinamide adenine dinucleotide (NAD + ) plays a crucial role as a coenzyme for electron transfer in energy metabolism. Decreased NAD + levels in myocardial cells lead to inadequate ATP production and increased susceptibility to heart failure. Researchers are exploring ways to increase NAD + levels to alleviate heart f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Extracellular NAMPT (eNAMPT) has emerged as a cytokine in pre-β-cell colony-enhancing factor (PBEF) that helps the maturation of β cells by activating Toll-like receptor 4 (TLR4) [ 36 ]. It was reported that pharmaceutically activated NAMPT in a diabetic mouse model decreased the NADH/NAD + ratio and improved overall cardiac function by improving p-AKT, p-eNOS, and Beclin 1 expression [ 37 ]. Overexpression of NAMPT can increase NAD + synthesis and ATP levels in cardiomyocytes to protect against myocardial injury due to in vitro myocardial ischemia and reperfusion [ 38 ].…”
Section: The Role Of Nampt In Cardiac Healthmentioning
confidence: 99%
“…Extracellular NAMPT (eNAMPT) has emerged as a cytokine in pre-β-cell colony-enhancing factor (PBEF) that helps the maturation of β cells by activating Toll-like receptor 4 (TLR4) [ 36 ]. It was reported that pharmaceutically activated NAMPT in a diabetic mouse model decreased the NADH/NAD + ratio and improved overall cardiac function by improving p-AKT, p-eNOS, and Beclin 1 expression [ 37 ]. Overexpression of NAMPT can increase NAD + synthesis and ATP levels in cardiomyocytes to protect against myocardial injury due to in vitro myocardial ischemia and reperfusion [ 38 ].…”
Section: The Role Of Nampt In Cardiac Healthmentioning
confidence: 99%